Customer Relationship Management Pada E-Commerce Toko Asyhana - Muhammad Rizky Asyhana Putra; Moh. Muhtarom; Sopingi (Prosiding Seminar Nasional Teknologi Informasi dan Bisnis, 2023)
At this time, the sales mechanism in Asyhana Stores is that customers still come directly to the store and choose which batik clothes to buy. This of course makes the marketing area to be limited. In addition, promotions carried out by Toko Asyhana still use word of mouth, not yet web-based, so many customers don't know about it. The problem with the sales process is that there is no system capable of marketing products online based on a website that is integrated with social media. For sales records and sales reports that have not been computerized, they are still being recorded in the general ledger. So that the shop owner experienced an error in the process of making sales reports. Therefore, in order to overcome these problems, a web-based e-commerce system is needed which can help make it easier for shop owners to manage sales and assist customers in making purchases of batik clothes at Asyhana Stores. By creating a web-based e-commerce system, customers can easily see the types of batik clothes being sold and can also buy online. So that it can make the buying and selling process easier and more efficient. Ease of shopping is something that can expedite and facilitate a business. With a web that has a CRM (Customer Relationship Management) feature, one of which is chat/messages, it can make Asyhana Stores more organized and increase sales profits.